Exploring Managers’ Perception Towards Generation Y Employees : A Case Study in an IT Company in Selangor - Saw Shuey, Yuin; Helmi, Sumilan; Florianna Lendai, Michael Mulok; Nik Norsyamimi, Md Nor (UNIMAS Publisher, 2019)
This study was conducted to explore the manager’s perception towards Generation Y employees particularly in the IT industry in Selangor. A case study approach was adopted in which data was obtained through semi-structured interviews. Purposive sampling technique was used and a total of eight (8) informants participated and interviewed. The data obtained from the interview were qualitatively analyzed. Data analysis was conducted by adopting a content analysis framework in which obtained data were divided into four (4) phases including condensation, code, category and inference and summarize. The findings showed majority of the managers perceived that openness to experience, conscientious and extraversion’ are the most common personalities among Generation Y employees. Besides that, the findings also revealed that in terms of work ethics, Generation Y employees are perceived as accountable of own’s actions, respect authority, transparency and loyal. The result of this study implicates the organization in terms of attrition and turnover rate among Generation Y employees and organizational branding. The result of this study provided some recommendations to HR practitioners and organizations in managing and handling at the workplace.